"Both Sides of the Wheelchair": The Views of Individuals with, and Parents of Individuals with Friedreich Ataxia Regarding Pre‐symptomatic Testing of Minors. Issue 5 (17th January 2015) - Lowe, Georgia C.; Corben, Louise A.; Duncan, Rony E.; Yoon, Grace; Delatycki, Martin B.
Abstract: Friedreich ataxia (FRDA) is an autosomal recessive neurodegenerative disorder characterized by variable age of onset, with no treatment proven to alter its natural history. Siblings of individuals with FRDA have a 25 % risk of developing the condition, raising issues around genetic testing of asymptomatic minors. There is a lack of professional consensus and limited empirical evidence to support provision or refusal of testing. This study aimed to ascertain the opinions of individuals with and parents of individuals with FRDA regarding pre‐symptomatic testing of minors. A qualitative research approach using semi‐structured interviews and thematic analysis was employed. Interviews with ten individuals with FRDA, and ten parents of individuals with FRDA were conducted, recorded, transcribed and analyzed. Four findings emerged. First, a number of arguments for and against testing minors were identified. Second, strong support existed from parents about the parental right to test their at‐risk immature children, but individuals with FRDA were of mixed opinions. Third, participants felt it was not the clinician's role to make a final decision about whether testing occurs. Finally, a specific issue of concern regarding testing was what and when to tell at‐risk children about the test result. The findings highlight a dilemma of how to manage the desires of some individuals and families affected by FRDA to access testing, when there is a lack of professional consensus due to differing opinions regarding autonomy, confidentiality and risk of harm. Research regarding the impact of testing and the views of at‐risk individuals and clinicians is required so an appropriate framework for dealing with this contentious issue is developed.